Open-labeled pilot study of cysteine-rich whey protein isolate supplementation for nonalcoholic steatohepatitis patients - Taned Chitapanarux (2018)
Background and Aims: Glutathione (GSH) depletion contributes to liver injury and development of steatohepatitis. Undenatured cysteine-rich whey protein isolate has been clinically proven to raise GSH in several patient groups. The aim of this study was to evaluate the effect of oral supplementation with whey protein on patients with nonalcoholic steatohepatitis (NASH). Methods: In an open-labeled clinical trial, 38 patients (18 male, 20 female; mean age 48 ± 14 years) with NASH confirmed by computed tomography measurements and liver biochemistries were given with a daily dose of 20 g whey protein isolate for 12 weeks. Results: A significant reduction in alanine aminotransferase (ALT) (64 ± 72 vs 46 ± 36, P = 0.016) and aspartate aminotransferase (AST) (45 ± 49 vs 33 ± 18, P = 0.047) were observed. Plasma glutathione and total antioxidant capacity increased significantly at the end of study (53 ± 11 vs 68 ± 11, P < 0.05 and 1.26 ± 0.10 vs 2.03 ± 0.10, P < 0.05). Liver attenuation index improved from -13.4 ± 11.1 to -9.7 ± 13.1 (P = 0.048). Hepatic macrovesicular steatosis decreased significantly after 12 weeks of supplementation (33.82 ± 12.82 vs 30.66 ± 15.96, P = 0.046). Whey protein isolate was well tolerated. No serious adverse events were observed. Conclusions: The results indicate that oral supplementation of cysteine-rich whey protein isolate leads to improvements in liver biochemistries, increased plasma GSH, total antioxidant capacity and reduced hepatic macrovesicular steatosis in NASH patients. The results support the role of oxidative stress in the pathogenesis of this disease. © 2009 Journal of Gastroenterology and Hepatology Foundation and Blackwell Publishing Asia Pty Ltd.